2009
DOI: 10.1042/bj20090427
|View full text |Cite
|
Sign up to set email alerts
|

NEMO oligomerization and its ubiquitin-binding properties

Abstract: The IKK [IκB (inhibitory κB) kinase] complex is a key regulatory component of NF-κB (nuclear factor κB) activation and is responsible for mediating the degradation of IκB, thereby allowing nuclear translocation of NF-κB and transcription of target genes. NEMO (NF-κB essential modulator), the regulatory subunit of the IKK complex, plays a pivotal role in this process by integrating upstream signals, in particular the recognition of polyubiquitin chains, and relaying these to the activation of IKKα and IKKβ, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 34 publications
(72 reference statements)
5
67
1
Order By: Relevance
“…1). The preference for linear ubiquitin chains is in agreement with previous studies, which showed that the NEMO-UBAN has an up to 100ϫ higher affinity to linear di-ubiquitin over Lys-63-, or Lys-48-linked di-ubiquitin (14,16,17). This might suggest that in a cellular environment where different ubiquitin chain types exist, e.g.…”
Section: Discussionsupporting
confidence: 81%
“…1). The preference for linear ubiquitin chains is in agreement with previous studies, which showed that the NEMO-UBAN has an up to 100ϫ higher affinity to linear di-ubiquitin over Lys-63-, or Lys-48-linked di-ubiquitin (14,16,17). This might suggest that in a cellular environment where different ubiquitin chain types exist, e.g.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, NEMO was reported to exist predominantly as a monomer in IKKα and IKKβ double knockout MEFs [92]. In contrast, a recent biochemical analysis indicates that an "apo" form of NEMO 1-355 missing the C-terminal ZF domain forms a dimer and a weaker tetramer, arising from self-association of the N-terminal domain, with an apparent K d of 25.6 µM (dimer-tetramer equilibrium) [93]. Moreover, addition of an IKK-derived NEMO-binding peptide eliminates the NEMO tetramer formation in vitro, thus suggesting that IKK prevents NEMO tetramerization.…”
Section: Nemo Structural Conundrummentioning
confidence: 99%
“…Since (i) ATM usually (although not absolutely) requires the S/ T-Q motif in its substrates for phosphorylation [94] and (ii) Q86N and Q86A point mutations of NEMO completely abrogate NF-κB activation by DNA-damaging agents without affecting activation by LPS [54], it can be concluded that the ATM accessibility of both S85 and Q86 residues is required to mediate S85 phosphorylation and NF-κB activation. Ivins et al [93] demonstrated that binding of diubiquitin at the NOA/NUB/UBAN domain induced a modest but measurable structural alteration in the N-terminal CC1 domain that is located ~200 aa away. This suggests the possibility that a binding event in a region away from the S85-Q86 motif may cause a conformational shift to permit efficient ATM accessibility to the SQ motif.…”
Section: Nemo Structural Conundrummentioning
confidence: 99%
See 2 more Smart Citations